2016
DOI: 10.1021/acsnano.5b06007
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive, Multiplex Raman Frequency Shift Immunoassay of Liver Cancer Biomarkers in Physiological Media

Abstract: Highly sensitive multiplex biomarker detection is critical for the early diagnosis of liver cancer. Here, a surface-enhanced Raman scattering (SERS) frequency-shift immunoassay is developed for detection of liver cancer biomarkers α-fetoprotein and Glypican-3 down to subpicomolar concentrations in saline solution. A high temperature modification of the Tollen's method affords silver nanoparticle films with excellent SERS response upon which ordered domains of Raman reporters are chemisorbed by microcontact pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
78
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 36 publications
2
78
2
Order By: Relevance
“…For example, a multiplex SERS frequency shift immunoassay for liver and pancreatic cancer biomarkers has already been developed with high sensitivity. 106 Nanoparticle films with an excellent SERS response have been fabricated capable of multiplexed detection of liver cancer biomarkers by recording two frequency shifts upon an assay. 106 In a similar manner, a separate study demonstrated that immobilization of functionalized gold nanoshells on a gold-coated silicon substrate led to a significant improvement in the SERS signal for pancreatic cancer biomarker detection.…”
Section: Adaptation and Incorporation Of Sers Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a multiplex SERS frequency shift immunoassay for liver and pancreatic cancer biomarkers has already been developed with high sensitivity. 106 Nanoparticle films with an excellent SERS response have been fabricated capable of multiplexed detection of liver cancer biomarkers by recording two frequency shifts upon an assay. 106 In a similar manner, a separate study demonstrated that immobilization of functionalized gold nanoshells on a gold-coated silicon substrate led to a significant improvement in the SERS signal for pancreatic cancer biomarker detection.…”
Section: Adaptation and Incorporation Of Sers Technologymentioning
confidence: 99%
“…106 Nanoparticle films with an excellent SERS response have been fabricated capable of multiplexed detection of liver cancer biomarkers by recording two frequency shifts upon an assay. 106 In a similar manner, a separate study demonstrated that immobilization of functionalized gold nanoshells on a gold-coated silicon substrate led to a significant improvement in the SERS signal for pancreatic cancer biomarker detection. 107 This work was used to detect three cancer biomarkers at concentrations as low as 2 ng ml −1 .…”
Section: Adaptation and Incorporation Of Sers Technologymentioning
confidence: 99%
“…Detection of tumor markers plays a significant role for early diagnosis, screening, and treatment of cancers. Techniques for tumor marker detection include CL , MS , electrophoresis , and immunoassays . Among them, immunoassays (e.g.…”
Section: Applications For Biomarker Detectionmentioning
confidence: 99%
“…Recently, surface-enhanced Raman scattering (SERS) based methods for multiple tumor biomarkers detection have got a lot of attentions because of its narrow 'fingerprint' Raman spectrum from analyte molecule, which enables the SERS to be utilized to recognize and quantify various targets from mixture [31]. With the development of various nanomaterials, SERS was utilized for detecting multiple cancer biomarkers successfully [32][33][34][35][36]. For example, in order to detect AFP and Glypican-3, Tang et al has used silver nanoparticle film as SERS substrate to design SERS frequency-shift immunoassay [32].…”
mentioning
confidence: 99%
“…With the development of various nanomaterials, SERS was utilized for detecting multiple cancer biomarkers successfully [32][33][34][35][36]. For example, in order to detect AFP and Glypican-3, Tang et al has used silver nanoparticle film as SERS substrate to design SERS frequency-shift immunoassay [32]. By taking advantages of gold nanoflowers and SERS-active magnetic nanoparticles, a sandwich immunoassay was designed by Song et al to detect CEA and NSE, which showed high specificity and sensitivity [33].…”
mentioning
confidence: 99%